Prostate volume’s effect on IPSS in patients over 50 with LUTS at RSUD Arjawinangun - Auliya Sabilla Rosyada; Yudi Amiarno; Ferdy Ardiansyah; Siti Maulidya Sari (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2024)
The prostate is a gland that is part of the male reproductive system, located just below the bladder and surrounding the urethra. The prostate plays a role in producing semen, which nourishes and transports sperm. The International Prostate Symptom Score (IPSS) is a self-administered questionnaire used to assess symptoms of Benign Prostatic Hyperplasia (BPH). This study evaluates the relationship between prostate volume measured through transabdominal ultrasound and the International Prostate Symptom Score (IPSS) in patients aged 50 and above with Lower Urinary Tract Symptoms (LUTS) at RSUD Arjawinangun. The method involves using primary data (questionnaires) and performing prostate volume measurements via transabdominal ultrasound on 20 patients. The data will then be analyzed using SPSS version 26 with Spearman's test. Univariate results show that 12 patients experienced severe IPSS scores. The characteristic of prostate volume measured by transabdominal ultrasound was most found to be normal, with 12 patients having this volume. There was no significant relationship between prostate volume and the International Prostate Symptom Score (IPSS) in patients aged 50 and above with Lower Urinary Tract Symptoms (LUTS) at RSUD Arjawinangun, with a p-value of 0.811.